Endomyocardial miR‐133a levels correlate with myocardial inflammation, improved left ventricular function, and clinical outcome in patients with inflammatory cardiomyopathy. (13th June 2016) - Besler, Christian; Urban, Daniel; Watzka, Stefan; Lang, David; Rommel, Karl‐Philipp; Kandolf, Reinhard; Klingel, Karin; Thiele, Holger; Linke, Axel; Schuler, Gerhard; Adams, Volker; Lurz, Philipp
Abstract: Aims: Inflammatory heart disease represents an important cause of chronic dilated cardiomyopathy (DCM). Predicting the clinical course of patients with inflammatory cardiomyopathy (iCMP) is difficult, and the prognostic value of current biological markers remains controversial. We tested whether expression of selected microRNAs in endomyocardial biopsies (EMBs) is related to LV functional recovery and clinical events in iCMP patients. Methods and results: EMBs were obtained from patients with iCMP ( n = 76) and non‐inflammatory DCM ( n = 22). A set of six microRNAs implicated in inflammation (miR‐155 and miR‐146b), heart failure (miR‐21 and miR‐133a), and endothelial cell (miR‐126) and skeletal muscle function (miR‐206) was pre‐defined. Endomyocardial expression of miR‐155 and miR‐133a, as quantified by reverse transcription–PCR (RT–PCR), was up‐regulated in patients with iCMP as compared with patients with DCM. Levels of miR‐133a ( R = 0.73, P < 0.01) and miR‐155 ( R = 0.63, P < 0.01) correlated with inflammatory cell count on EMBs from patients with iCMP. Patients with iCMP and preserved LV function at study entry demonstrated higher expression of miR‐133a than patients with reduced LV function. Also, increased expression of miR‐133a was associated with less fibrosis and myocyte necrosis on EMB, and LV functional recovery during a mean follow‐up of 3.1 years. Importantly, patients with iCMP and miR‐133a levels in the upper tertile showed longer survival free of death, malignant arrhythmias, and hospitalizations for heart failure. Conclusion: The present study demonstrates that miR‐133a levels correlate with macrophage infiltration, cardiac injury, improved LV function, and clinical outcome in patients with iCMP. miR‐133a may serve as a potential novel biomarker and therapeutic target in human iCMP.